2018
DOI: 10.3390/jcm8010007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cellular Trafficking of Fibroblast Growth Factor Receptors as a Strategy for Selective Cancer Treatment

Abstract: Fibroblast growth factor receptors (FGFRs) in response to fibroblast growth factors (FGFs) transmit signals across the cell membrane, regulating important cellular processes, like differentiation, division, motility, and death. The aberrant activity of FGFRs is often observed in various diseases, especially in cancer. The uncontrolled FGFRs’ function may result from their overproduction, activating mutations, or generation of FGFRs’ fusion proteins. Besides their typical subcellular localization on the cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
62
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 206 publications
(286 reference statements)
0
62
0
3
Order By: Relevance
“…The mechanisms involved in FGFR1 internalization are only partially understood [29]. It was demonstrated that FGFR1 is subjected to constitutive, low‐rate internalization, however, FGFR1 dimerization caused by ligand binding largely accelerates uptake of the receptor [30–33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms involved in FGFR1 internalization are only partially understood [29]. It was demonstrated that FGFR1 is subjected to constitutive, low‐rate internalization, however, FGFR1 dimerization caused by ligand binding largely accelerates uptake of the receptor [30–33].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that FGFR1 is subjected to constitutive, low‐rate internalization, however, FGFR1 dimerization caused by ligand binding largely accelerates uptake of the receptor [30–33]. The efficiency and mechanism of FGFR1 internalization depend on the type of an applied ligand [29,34–39]. The uptake of FGF/FGFR1 complexes mainly occurs via clathrin‐mediated endocytosis (CME) leading to lysosomal degradation of FGFR1 [29,30,36,37,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FGFRs-FGFs signaling is important for angiogenesis, regulation of metabolism and tissue repair [1][2][3]. The dysregulation of FGFRs leads to developmental disorders and cancer [4][5][6][7]. FGFR1 is overexpressed in lung cancers, breast cancers, osteosarcomas and in solid tumors like head and neck cancers, and it is associated with poor patient prognosis [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their importance in cellular homeostasis, the expression and activity of RTKs is finely tuned, and any aberrancy in their signalling leads to disease development. Chromosomal rearrangements, gene amplifications, gain of function, alternative splicing, and autocrine activation are among the most frequent causes of oncogenic RTK signalling [ 2 , 3 ]. Among the RTKs, the fibroblast growth factor–fibroblast growth factor receptor (FGF–FGFR) axis has attracted considerable attention as a druggable target, and several therapeutic strategies have been developed for its selective targeting in cancer [ 4 ].…”
mentioning
confidence: 99%